2020
DOI: 10.1016/j.sleep.2020.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Validation of sleep stage classification using non-contact radar technology and machine learning (Somnofy®)

Abstract: Objective: To validate automatic sleep stage classification using deep neural networks on sleep assessed by radar technology in the commercially available sleep assistant Somnofy® against polysomnography (PSG). Methods: Seventy-one nights of overnight sleep in healthy individuals were assessed by both PSG and Somnofy at two different institutions. The Somnofy unit was placed in two different locations per room (nightstand and wall). The sleep algorithm was validated against PSG using a 25-fold cross validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 23 publications
1
66
2
2
Order By: Relevance
“…Therefore, the statistical analyses exploring whether the reciprocal associations between sleep, mental strain, and training load are moderated by sleeper category (good vs. poor) should be interpreted with caution. Last, although the device used for sleep monitoring used in the current study performed well in the validation study against PSG, the relationship of the Somnofy-derived sleep parameters and PSG data is not perfect ( Toften et al, 2020 ). Hence, some measurement error regarding the sleep variables should be acknowledged.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, the statistical analyses exploring whether the reciprocal associations between sleep, mental strain, and training load are moderated by sleeper category (good vs. poor) should be interpreted with caution. Last, although the device used for sleep monitoring used in the current study performed well in the validation study against PSG, the relationship of the Somnofy-derived sleep parameters and PSG data is not perfect ( Toften et al, 2020 ). Hence, some measurement error regarding the sleep variables should be acknowledged.…”
Section: Discussionmentioning
confidence: 91%
“…Still, Somnofy seems to provide more accurate sleep staging than several comparable non-obtrusive sleep assessment alternatives ( Peake et al, 2018 ). For a full technical overview of the sleep monitor, including its limitations and results of its validation, see Toften et al, 2020 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system can detect movements of less than 1 mm and can be used with very high sensitivity and specificity for detecting sleep-wake state compared with polysomnography (Toften 2020). It avoids the use of any other remote approaches, such as visual observation by cameras, and is well-tolerated among patients.…”
Section: Major Innovationmentioning
confidence: 99%
“…Recently, a full validation of Somnofy against the gold standard in sleep measurement -manually scored polysomnography (PSG) was carried out. The study has shown Somnofy to be an adequate measure of sleep and wake, as well as sleep stages, in a healthy adult population (Toften et al, 2020). For the purposes of this study, the following sleep variables were obtained from the Somnofy sleep monitor: sleep onset, sleep offset, time in bed, sleep onset latency, total sleep time, time and percentage in sleep stages (light, deep and REM), sleep efficiency, and respiration rate (RP).…”
Section: Instrumentsmentioning
confidence: 99%